2018
DOI: 10.7759/cureus.2792
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Myocarditis Demonstrated Using Cardiac Magnetic Resonance Imaging in a Patient with Eosinophilic Granulomatosis with Polyangiitis (Churg-Strauss Disease)

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA), historically known as the Churg-Strauss disease, is a small- to medium-sized vessel multi-organ vasculitis with a propensity to involve the heart. EGPA is a rare condition with an estimated annual incidence of one to 4.2 people per million. The cardiac involvement causes significant morbidity and mortality in EGPA patients. Approximately 50% of the deaths in EGPA are related to cardiac disease and occur within the first few months since diagnosis. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…The study conclusively demonstrated the strengths of CMR use as part of a new strategy to treat these patients before the progression of damage becomes insurmountable. Also, the patient in that study did not show any areas of stenosis, calcified plaque, or soft plaque upon evaluation with CTA [26]. The use of CMR has proven to be the most effective imaging technique and diagnostic tool for evaluating cardiovascular disease in EGPA patients.…”
Section: Cmr Performance Compared To Other Imaging Modalitiesmentioning
confidence: 70%
See 3 more Smart Citations
“…The study conclusively demonstrated the strengths of CMR use as part of a new strategy to treat these patients before the progression of damage becomes insurmountable. Also, the patient in that study did not show any areas of stenosis, calcified plaque, or soft plaque upon evaluation with CTA [26]. The use of CMR has proven to be the most effective imaging technique and diagnostic tool for evaluating cardiovascular disease in EGPA patients.…”
Section: Cmr Performance Compared To Other Imaging Modalitiesmentioning
confidence: 70%
“…The same study showed that CMR detected cardiac abnormalities with higher sensitivity than ECG (88% versus 82%) [25]. A study by Dalia et al also indicated CMR's capability when a patient with cardiovascular involvement in EGPA exhibited apical hypokinesis with an EF of 55% [26]. However, upon evaluation with CMR, there were several areas of delayed enhancement in the LV myocardium, and decreased perfusion in mid to apical septal and inferior segments through the cardiac apex [26].…”
Section: Cmr Performance Compared To Other Imaging Modalitiesmentioning
confidence: 93%
See 2 more Smart Citations
“…A second group detailed a case of cardiac tamponade leading to a new diagnosis of EGPA, even rarer than myopericarditis, and indicative of increased severity of disease 15. In all cases, the increasingly recognised role for CMRI is highlighted7 16 although this does not form part of the official guidelines for the management of EGPA, and more extensive studies are certainly warranted for its use in this setting, especially given the paucity of data, mostly derived from individual case reports.…”
Section: Discussionmentioning
confidence: 99%